Pengaruh Corporate Social Responsibility, Ukuran Perusahaan, Dan Solvabilitas Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur Sektor Barang Konsumsi Yang Terdaftar Di BEI Periode 2018-2021 - Komang Pande Rita Septiani; Made Arie Wahyuni (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the influence of corporate social responsibility, company size, and solvency on the financial performance of manufacturing companies in the consumer goods sector listed on the IDX for the 2018-2021 period. This study used quantitative methods with secondary type data. The data is in the form of an annual report obtained from the Indonesia Stock Exchange website, namely www.idx.co.id. Sample determination was carried out by purposive sampling method with certain criteria and obtained 72 company samples. The analysis technique used is multiple linear regression analysis using SPSS software version 25. The results showed that: (1) partially corporate social responsibility did not have a significant effect on financial performance, (2) partially the size of the company had a significant positive effect on financial performance, (3) partially solvency had a significant negative effect on financial performance.